A construção do telejornalismo de vizinhança da Rede Globo: um estudo comparativo de três emissoras afiliadas no Centro-Oeste - Sousa, Bernadete Coelho de (2022)
In this research work it is proposed to present a reflection on the subject of telejournalism self-styled 'community' of Rede Globo from its development in broadcasters that are part of Rede Globo's affiliate network in the Midwest Region, specifically journalistic material that involves issues related to the promotion of citizenship in these newscasts. The observation has a comparative character and, depending on the current situation, the period chosen was that of June and July 2020, which corresponded (albeit unintentionally) to the period of Covid-19 pandemic. It should be noted that, even with the serious situation of the coronavirus, in that period the local broadcasters kept the space for the so-called 'community journalism', although adapting to new productive routines, since the pandemic affected the structures, agendas and contents of journalism. The object of analysis was the news broadcast at lunchtime/midday on broadcasters: TV Anhanguera - Goiânia/GO, TV Morena Campo Grande/MT and TV Centro América/MS. sought verify/compare how stations belonging to the same network effectively carry out/interpret the proposal of community telejournalism in their local products and how they seek to highlight the demands of the community. The methodology used is base content analysis; It is a research method and technique that has been present since the first studies of communication research where the investigation of phenomena is sought symbolic collecting data that lead to understanding and/or inference that facilitate the understanding of the context. The investigation shows how the term 'community' associated with ‘citizenship’ is used differently on each broadcaster, but prevails as a strategy to strengthen the ties of affinity with the viewer and create symbolic value with the court hearing. As a result of the analysis, it was observed that citizen participation prevails as someone who is in a subordinate position, a social actor with demands for health services. infrastructure that are the responsibility of the State.The conclusion points out that journalism self-styled 'community' journalism is primarily a neighborhood journalism, in which individuals from the same locality, without organic or organizational ties, unite in sporadic way to claim a service to the public power. It was noted that the way this journalism is presented on broadcasters in the Midwest and seeks to foster the notion that the interviewees share values, interests and beliefs and, therefore, belong to a community. It was also observed that there is no single formula to be followed, but that each of the stations surveyed sought, in their own way, to give visibility to the problems of infrastructure of peripheral neighborhoods, thus following the determination of Rede Globo.